Employee Performance Evaluation at PT WIKA Based on Service Quality and Customer Satisfaction - Ayulita Purnama Sari; Murpin Josua Sembiring; David Sukardi Kodrat (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to evaluate customer satisfaction with employee performance at PT WIKA based on service quality dimensions using Service Quality (SERVQUAL) and Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) based decision support system approaches. Research Methodology: This study employed a quantitative descriptive method by integrating SERVQUAL with the MOORA decision-support system. Data were collected through questionnaire-based surveys distributed to 100 PT WIKA customers using 20 service quality indicators representing the tangibility, reliability, responsiveness, assurance, and empathy dimensions. The analysis compared customer perception and expectation scores to identify satisfaction gaps and determine the priority service dimensions. Results: The findings revealed that the average SERVQUAL satisfaction ratio was 1.01, indicating that overall service performance generally met customer expectations. A total of 14 out of 20 indicators (67%) were categorized as satisfactory, while six indicators (33%) remained unsatisfactory. Furthermore, the MOORA analysis identified reliability as the most dominant service quality dimension contributing to customer satisfaction and employee performance evaluations. Conclusions: Overall, customers were satisfied with the employee performance at PT WIKA. However, several indicators related to responsiveness and service consistency require improvement to enhance customer satisfaction. Limitations: This study was limited to a single company and a specific customer sample, which may reduce the generalizability of its findings. In addition, the weighting process in the MOORA method is determined subjectively. Contributions: This study contributes to service quality and human resource management literature by integrating SERVQUAL and MOORA in evaluating employee performance and supporting service improvement decision-making